Perception and Acceptance of Risk for Online Learning: Digitalization - KHALID, NOR RAHIMY; Suraya Akmar Mokhtaruddin; Zanatul Shima Aminuddin (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study determines the acceptance of online learning by identify the intention applied online learning. The study identifies the perception of risk and acceptance of risk for intention to use online learning. A questionnaire was voluntarily completed by 452 undergraduate technical and vocational students, online education has been generally accepted during covid 19 pandemic. The finding from structural equation modelling analyses indicated that perception of risk positively influence intention to use online learning and acceptance of risk negatively influence online learning. Furthermore, it proves that online learning is convenience and student prefer to enroll in synchronous and asynchronous online, however the negative relationship between acceptance of risk for intention to use online learning indicate that. Unwillingness for physical class due to mobility and safety. The findings of this study are remarkable to understand the acceptance of online learning that leads to digital nation in future. Online learning had accelerated the speed of digitalization. Digital is convenience and create a flexibility. Furthermore, digitalization creates a trend worldwide and gain more popularity.